The handbook of research on scalable computing technologies - Li, Kuan-Ching; Hsu, Ching-Hsien 1963-; Yang, Laurence Tianruo; Dongarra, Jack 1950-; Zima, Hans 1941- (Information Science Reference, 2010)
"This book presents, discusses, shares ideas, results and experiences on the recent important advances and future challenges on enabling technologies for achieving higher performance" - Provided by publisher
Includes bibliographical references and index
Keywords: Skalierbarkeit; Programmierung; Aufsatzsammlung